Nile Tilapia Skin Impregnated with Antibacterial Silver/Titanium Dioxide Compounds - Maíra Cristina Marcolino; Milena Lima Guimarães; Jorge Alexandre Alencar Fotius; Leda Maria Saragiotto Colpini; Mateus Matiuzzi da Costa; Helinando Pequeno de Oliveira (Applied Microbiology, 2023)
The development of alternative (and free-of-antibiotics) antibacterial and antibiofilm agents is an important strategy to circumvent the resistance of bacteria to antibiotics. Herein, we explore the production of mixed oxides by incorporating silver nanoparticles in titanium dioxide as a silver concentration-dependent antibacterial agent that is further incorporated in Tilapia fish skin (a promising prototype of xenograft), integrating the antibacterial activity of mixed oxide into the intrinsic properties of Tilapia skin. The antibiofilm activity of samples prepared with high concentrations of silver (10 wt% of precursor AgNO3) has been considered a good antibiofilm response. The influence of silver content is also observed with respect to the minimum bactericidal concentration, which is reduced to 3.13 mg/mL with a characteristic kill time in the order of 30 min that is associated with antibiofilm activity in biofilm-forming strains of Staphylococcus aureus. These results indicate that modified Tilapia fish skin acquires antibacterial behavior and can be explored for xenografts with prospective applications in the light-dependent actuation of TiO2-based compounds.